Quantum anomalous Hall phase in a one-dimensional optical lattice. (27th February 2018) - Liu, Sheng; Shao, L B; Hou, Qi-Zhe; Xue, Zheng-Yuan
Abstract: We propose to simulate and detect quantum anomalous Hall phase with ultracold atoms in a one-dimensional optical lattice, with the other synthetic dimension being realized by modulating spin–orbit coupling. We show that the system manifests a topologically nontrivial phase with two chiral edge states which can be readily detected in this synthetic two-dimensional system. Moreover, it is interesting that at the phase transition point there is a flat energy band and this system can also be in a topologically nontrivial phase with two Fermi zero modes existing at the boundaries by considering the synthetic dimension as a modulated parameter. We also show how to measure these topological phases experimentally in ultracold atoms. Another model with a random Rashba and Dresselhaus spin–orbit coupling strength is also found to exhibit topological nontrivial phase, and the impact of the disorder to the system is revealed.